THE ROLE OF COHESION IN RECOUNT TEXTS : A CASE STUDY OF SECOND SEMESTER STUDENTS OF STMIK PROVISI IN ENGLISH 2 WRITING ASSIGNMENT - Qorinta Shinta (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2010)
This study is a descriptive research aiming at discovering towhat extent students applied cohesion in recount texts in their writingassignment. The participants were STMIK PROVISI students takingEnglish 2. Data were taken from students’ writing assignments in June2008 and they were gathered by applying qualitative methods. Resultsindicated that most students were relatively aware of the stages in recounttexts even though some of them applied past and present tensesinterchangeably without any logical reasons. Referring to cohesivedevices, the students mostly used anaphoric reference, personal reference,and demonstrative reference, as well as simple additive conjunction.